(untitled) - Julio Sanchez (New York, 1995)
The dynamics of computer graphics; Graphical image structures; Operations on geometrical images; Bitmap image acquisition and encoding; Animation in VGA graphics; VGA drivers for standard modes; VGA mode X drivers and primitives; XGA architecture and initialization; XGA drivers and primitives...
Keywords: MS - DOS ( computer file ),Windows ( computer programs ),computer animation